Management Strategies to Improve Organizational Performance in the Digital Age - Utami, Istri (PT. Anagata Sembagi Education, 2025)
This study aims to examine management strategies to improve organizational performance in the digital era by emphasizing the integration of technology into managerial processes. The method used is descriptive qualitative research through in-depth interviews, observation, and documentation with informants consisting of leaders, heads of IT divisions, staff, and HR departments. The results of the study indicate that digital-based management strategies include planning using data analytics, organizing through an adaptive organizational structure, digital leadership that encourages technological literacy, and control based on a digital monitoring system. The main supporting factors for the success of this strategy are leadership support, an innovative organizational culture, and adequate technological infrastructure, while inhibiting factors include limited digital literacy, resistance to change, and budget constraints. This study concludes that digital management strategies not only improve work efficiency and effectiveness but also strengthen organizational competitiveness in the digital era.